Adding Value to Second-Language Listening and Reading Subscores: Using a Score Augmentation Approach. Issue 3 (3rd July 2018) - Papageorgiou, Spiros; Choi, Ikkyu
Abstract : This study examined whether reporting subscores for groups of items within a test section assessing a second-language modality (specifically reading or listening comprehension) added value from a measurement perspective to the information already provided by the section scores. We analyzed the responses of 116, 489 test takers to reading and listening items from operational administrations of two large-scale international tests of English as a foreign language. To "strengthen" the reliability of the subscores, and thus improve their added value, we applied a score augmentation method (Haberman, 2008). In doing so, our aim was to examine whether reporting augmented subscores for specific groups of reading and listening items could improve the added value of these subscores and consequently justify providing more fine-grained information about test taker performance. Our analysis indicated that in general, there was lack of support for reporting subscores from a psychometric perspective, and that score augmentation marginally improved the added value of the subscores. We discuss several implications of our findings for test developers wishing to report more fine-grained information about test performance. We conclude by arguing that research on how to best report such refined feedback should remain the focus of future efforts related to second-language proficiency tests.